Floristic composition and carbon stock estimation under restored mangrove area in Bagan Serdang, North Sumatra, Indonesia - MELINDA SURIANI HAREFA; ZULKIFLI NASUTION; ELING TUHONO; ARIDA SUSILOWATI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Harefa MS, Nasution Z, Tuhono E, Susilowati A. 2023. Floristic composition and carbon stock estimation under restored mangrove area in Bagan Serdang, North Sumatra, Indonesia. Biodiversitas 24: 2037-2044. Mangrove forests play an important role in the surrounding ecosystem, providing various complex ecosystem services such as coastal protection, food and medicine provision, water quality improvement, and habitat for various terrestrial and aquatic biota. However, forest degradation and conversion have destroyed the majority of mangrove habitats. Monoculture restoration of mangroves with local species has been carried out in various areas, including Bagan Serdang village in North Sumatra, to restore the degraded area. However, fewer studies have been conducted to assess the floristic diversity of monoculture restoration areas and their carbon stock storage estimation, especially in North Sumatra. This research aims to analyze vegetation diversity and estimate carbon stocks in a restoration area dominated by Avicennia marina (Forssk.) Vierh. species in Bagan Serdang village, North Sumatra, Indonesia. Purposive sampling was employed to identify species and measure tree diameter at breast height by creating plot lines that filled the observation area with 10 x 10 plots. Therefore, the Shannon Wiener diversity index (H') and allometric equations were used to determine mangrove diversity and biomass. The study's findings revealed that A. marina had the highest Importance Value Index (IVI) at all growth stages, including seedlings, saplings, and trees, with values of 89.12, 190.91, and 263.14%, respectively. The seedling stages had the highest diversity, with a value of 1.241. The total amount of CO2 absorbed is 200.67 tons/ha, and the total amount of carbon stored is 54.67MgC H-1.